A Unifying Concept for the Quantitative Assessment of Secondary Mitral Regurgitation - Bartko, Philipp E.; Arfsten, Henrike; Heitzinger, Gregor; Pavo, Noemi; Toma, Aurel; Strunk, Guido; Hengstenberg, Christian; Hülsmann, Martin; Goliasch, Georg (Journal of the American College of Cardiology, 2019)
Diverging guideline definitions for the quantitative assessment of severe secondary mitral regurgitation (sMR) reflect the lacking link of the sMR spectrum to mortality and has introduced a source of uncertainty and continuing debate. The current study aimed to define improved risk-thresholds specifically tailored to the complex nature of sMR that provide a unifying solution to the ongoing guideline-controversy. This study enrolled 423 heart failure patients under guideline-directed medical therapy and assessed sMR by effective regurgitant orifice area (EROA), regurgitant volume (RegVol), and regurgitant fraction (RegFrac). Measures of sMR severity were consistently associated with 5-year mortality with a hazard ratio of 1.42 for a 1-SD increase (95% confidence interval [CI]: 1.25 to 1.63; p < 0.001) for EROA, 1.37 (95% CI: 1.20 to 1.56; p < 0.001) for RegVol, and 1.50 (95% CI: 1.30 to 1.73; p < 0.001) for RegFrac. Results remained statistically significant after bootstrap- or clinical confounder-based adjustment. Spline-curve analyses showed a linearly increasing risk enabling the ability to stratify into low-risk (EROA <20 mm2 and RegVol <30 ml), intermediate-risk (EROA 20 to 29 mm2 and RegVol 30 to 44 ml), and high-risk (EROA ≥30 mm2 and RegVol ≥45 ml) groups. In the intermediate-risk group, a RegFrac ≥50% as indicator for hemodynamic severe sMR was associated with poor outcome (p = 0.017). A unifying concept based on combined assessment of the EROA, the RegVol, and the RegFrac showed a significantly better discrimination compared with the currently established algorithms. Risk-based thresholds tailored to the pathophysiological concept of sMR provide a unifying solution to the ongoing guideline controversy. An algorithm based on the combined assessment of the unifying cutoffs for EROA, RegVol, and RegFrac improves risk prediction compared with currently established grading. [Display omitted]